2008
DOI: 10.1038/bjp.2008.236
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline toxicity to cardiomyocytes or cancer cells is differently affected by iron chelation with salicylaldehyde isonicotinoyl hydrazone

Abstract: Background and purpose: The clinical utility of anthracycline antineoplastic drugs is limited by the risk of cardiotoxicity, which has been traditionally attributed to iron-mediated production of reactive oxygen species (ROS). Experimental approach: The aims of this study were to examine the strongly lipophilic iron chelator, salicylaldehyde isonicotinoyl hydrazone (SIH), for its ability to protect rat isolated cardiomyocytes against the toxicity of daunorubicin (DAU) and to investigate the effects of SIH on D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…More recently, the oxidative stress hypothesis has been challenged by the absence of a cardio-protective effect of antioxidant drugs [23] and by the demonstration that the mechanisms of cardioprotection of dexrazoxane and of other iron chelators do not involve a decrease in free radicals formation [24]. Therefore, the contribution of iron to doxorubicin cardiotoxicity does not seem to be totally dependent on free radical formation, and other mechanisms related to anthracycline-induced heart iron accumulation are probably important, especially in the setting of chronic cardiac damage [9].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the oxidative stress hypothesis has been challenged by the absence of a cardio-protective effect of antioxidant drugs [23] and by the demonstration that the mechanisms of cardioprotection of dexrazoxane and of other iron chelators do not involve a decrease in free radicals formation [24]. Therefore, the contribution of iron to doxorubicin cardiotoxicity does not seem to be totally dependent on free radical formation, and other mechanisms related to anthracycline-induced heart iron accumulation are probably important, especially in the setting of chronic cardiac damage [9].…”
Section: Discussionmentioning
confidence: 99%
“…The observed protection with SIH against both DAU and H 2 O 2 was dependent on iron chelation, as it could be blunted by increasing the concentration of iron salts in the incubation medium. However, while SIH completely abolished the H 2 O 2 -induced significant increase of a lipid peroxidation marker, the protection by SIH against DAU cardiotoxicity was not accompanied by any significant change in this parameter (243).…”
mentioning
confidence: 80%
“…as protectors against ANT-induced cardiotoxicity in vitro and/or in vivo (see below), have been also shown not to blunt the antiproliferative effects of ANTs in various cancer cell lines (209,243,256). It should be noted that-with the exception of few DEX analogs (108)-no chelator has been specifically designed for use in prevention of ANT cardiotoxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Iron chelators are also of clinical interest in treating complications of transfusion-dependent b-thalassemia iron overload [2,7]. The structurally related SIH (salicylaldehyde isonicotinoyl hydrazone) has shown some partial daunorubicin cardioprotective activity in vitro [8] and in vivo at lower doses, though not at higher doses [9]. We previously showed that the clinically approved pro-drug iron chelator doxorubicin cardioprotective agent dexrazoxane (ICRF-187, Zinecard TM , Totect TM , Savene TM , Fig.…”
Section: Dp44mtmentioning
confidence: 99%